LANDSKAP DWIBAHASA YANG TERDAPAT PADA TEMPAT-TEMPAT UMUM DI KOTA BANDUNG: ANALISIS SOSIOLINGUISTIK - Ahmad Yani; Ria Utami (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2019)
This article aims to identify types of bilingual landscapes based on their contents, to describe the forms of the language use, and to describe the composition of language used. The objects of this study were 174 bilingual landscapes found around the city of Bandung, West Java, Indonesia taken from a number of different public places (campuses, hospitals, streets, commercial areas, stations, and restaurants). Data were taken based on simple random sampling. Data were analised using descriptive statistic. The results of the study showed that of the 174 bilingual landscapes data, the types of landscapes could be classified into six categories: General Information with 78 landscapes (44.82%), followed by Promotion with 56 landscapes (32.18%), Procedures 16 landscapes (9.20%), Prohibition 14 landscapes (8.04%), Request 6 landscapes (3.44%), and Thank You expressions 3 landscapes (1.72%) and Congratulation 1 landscape (0.57%). On the forms of language use, the finding showed that there were three forms of use (Translation, Code Switching/Code Mixing, and Transliteration).